1985
DOI: 10.1038/hdy.1985.29
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity and developmental stability in gynogenetic diploid and triploid rainbow trout

Abstract: We have previously reported that rainbow trout (Salmo gairdneri) more heterozygous at enzyme loci generally show increased developmental stability, as measured by reduced fluctuating asymmetry. We experimentally produced gynogenetic diploid and triploid individuals to test the effect of extreme heterozygosities on developmental stability. Gynogenetic diploids are identical by descent at an estimated 34 per cent of all loci and show a 50 per cent increase in the mean proportion of traits asymmetric per individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 23 publications
1
52
2
Order By: Relevance
“…Fluctuating asymmetry is defined as minor random deviations from perfect bilateral symmetry, as evidenced by measurable differences between the right and left sides of single characters on single individuals (Van Valen, 1962). Because both sides of a character are the products of expression of a single genome, such departures from bilateral symmetry presumably reflect the inability of the genome to coordinate development precisely; that is, fluctuating asymmetry reflects non-heritable developmental "noise" (Mather, 1953;Lerner, 1954;Van Valen, 1962;Soulé, 1979, 1982; Leamy, 1984;Leary et a!., 1985a;Palmer, 1986). Several studies have suggested that high levels of fluctuating asymmetry are likely to be associated with a decrease in individual fitness (Soulé, 1982;Leary et a!., 1984Leary et a!., , 1985bClarke and McKenzie, 1987; see also Bruckner, 1976), a result that is expected if developmental stability is an important component of fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuating asymmetry is defined as minor random deviations from perfect bilateral symmetry, as evidenced by measurable differences between the right and left sides of single characters on single individuals (Van Valen, 1962). Because both sides of a character are the products of expression of a single genome, such departures from bilateral symmetry presumably reflect the inability of the genome to coordinate development precisely; that is, fluctuating asymmetry reflects non-heritable developmental "noise" (Mather, 1953;Lerner, 1954;Van Valen, 1962;Soulé, 1979, 1982; Leamy, 1984;Leary et a!., 1985a;Palmer, 1986). Several studies have suggested that high levels of fluctuating asymmetry are likely to be associated with a decrease in individual fitness (Soulé, 1982;Leary et a!., 1984Leary et a!., , 1985bClarke and McKenzie, 1987; see also Bruckner, 1976), a result that is expected if developmental stability is an important component of fitness.…”
Section: Introductionmentioning
confidence: 99%
“…This type of asymmetry results from the inability of individuals to develop precisely along genetically determined pathways since both sides ofindividuals reflect the same genome. Fluctuating asymmetry, therefore, can be used as a measure of developmental stability (Mather, 1953;reviewed by Soule and Cuzin-Roudy, 1982;Leary et al, 1985b). Higherlevels offluctuating asymmetry indicate reduced developmental stability.…”
mentioning
confidence: 99%
“…The existence of such radical differences in primary biological structure (Benfey 1999) suggests that integrated physiological functioning might be impaired but that these negative effects might be offset by positive fitness related effects of increased genetic diversity (Leary et al 1985;Allendorf and Leary 1984), reallocation of energy to somatic growth, gene dosage effects (genetic expression directly proportional to ploidy) and/or protection from mutagenic events (Thorgaard et ai. 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to diploids, these include: 1) nuclear enlargement with triploids containing 50% more DNA, 2) larger cell size with approximate maintenance of the nuclear:cytoplasmic ratio along with a reduction in the surface areaivolume ratio, 3) fewer cells, but maintenance of diploid tissue, organ and body size and 4) increased allelic diversity with potentially three different alleles at each locus (Swarup 1959a;Leary et al 1985;Benfey 1999). These conditions suggest that triploids may experience potentially positive fitness or production related effects due to increased allelic diversity, higher genetic expression of growth related loci and somatic reallocation of energy normally invested in the maturational process.…”
Section: General Introductionmentioning
confidence: 99%
See 1 more Smart Citation